A phase II study of frontline paclitaxel/carboplatin/bevacizumab, paclitaxel/carboplatin/temsirolimus, or ixabepilone/carboplatin/bevacizumab in advanced/recurrent endometrial cancer - Aghajanian, Carol; Filiaci, Virginia; Dizon, Don S.; Carlson, Jay W.; Powell, Matthew A.; Secord, Angeles Alvarez; Tewari, Krishnansu S.; Bender, David P.; O'Malley, David M.; Stuckey, Ashley; Gao, JianJiong; Dao, Fanny; et al. (Gynecologic oncology, 2018)
Paclitaxel and carboplatin (PC) is a standard initial therapy for advanced endometrial cancer. We evaluated the efficacy and tolerability of incorporating three novel agents into initial therapy. In this randomized phase II trial, patients with chemotherapy-naïve stage III/IVA (with measurable disease) and stage IVB or recurrent (with or without measurable disease) endometrial cancer were randomly assigned to treatment with PC plus bevacizumab (Arm 1), PC plus temsirolimus (Arm 2) or ixabepilone and carboplatin (IC) plus bevacizumab (Arm 3). The primary endpoint was progression-free survival (PFS). Comparable patients on the PC Arm of trial GOG209 were used as historical controls. Secondary endpoints were response rate, overall survival (OS), and safety. Overall, 349 patients were randomized. PFS duration was not significantly increased in any experimental arm compared with historical controls (p > 0.039). Treatment HRs (92% CI) for Arms 1, 2, and 3 relative to controls were 0.81 (0.63–1.02), 1.22 (0.96–1.55) and 0.87 (0.68–1.11), respectively. Response rates were similar across arms (60%, 55% and 53%, respectively). Relative to controls, OS duration (with censoring at 36 months), was significantly increased in Arm 1 (p < 0.039) but not in Arms 2 and 3; the HRs (92% CIs) were 0.71 (0.55–0.91), 0.99 (0.78–1.26), and 0.97 (0.77–1.23), respectively. No new safety signals were identified. Common mutations and rates of mismatch repair protein loss are described by histotype. Potential predictive biomarkers for temsirolimus and bevacizumab were identified. PFS was not significantly increased in any experimental arm compared to historical controls. NRG Oncology/Gynecologic Oncology Group Study GOG-86P. •Paclitaxel + carboplatin is standard initial therapy for advanced endometrial cancer.•We assessed combinations with bevacizumab, temsirolimus or ixabepilone.•PFS was not significantly improved compared to historical control.